Search for antibacterial activity in a number of new S-derivatives (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines - Yu. V. Karpenko; O. I. Panasenko (Zaporozhye State Medical University, 2021)
The relevance of the study of 1,2,4-triazole derivatives with pyrimidine fragment is due to the synthesis of potential broad-spectrum antibacterial drugs, low molecular weight inducers of interferon, and antitumor agents, search for molecular descriptors of their structure, important for establishing patterns "structure - biological activity". The aim of the work is a computer search for the antibacterial action of new hybrids of 1,2,4-triazole-3(2H)-thiol with a pyrimidine fragment in relation to 5 test cultures, to establish the dependence of "structure - action". Materials and methods. For an in-depth study of the antibacterial activity of derivatives of 1,2,4-triazole-3(2H)-thiol hybrids with a pyrimidine fragment, 4 test cultures of museum strains of gram-positive, gram-negative bacteria and one species of fungi were selected. In silico studies were performed using regression and classification QSAR models. Results. Derivatives of 1,2,4-triazole-3(2H)-thiol hybrids with a pyrimidine moiety showed high antibacterial activity against gram-negative microorganisms (E. coli, P. aeruginosa). The obtained experimental results allowed to establish not only the role of the main structural features of the compounds in the manifestation of antimicrobial properties, but also to evaluate the effectiveness of the created classification and regression QSAR models. Based on the presented parameters for individual predictive QSAR models, it is possible to conclude about the effectiveness, stability and feasibility of using these models to search for new S-derivatives (1,2,4-triazole-3(2H)-yl)methyl)thiopyrimidines as promising antimicrobial agents. Conclusions. It was found that the studied derivatives of hybrids of 1,2,4-triazole-3(2H)-thiol with a pyrimidine fragment showed high antibacterial activity against gram-negative microorganisms. The developed QSAR classification models based on the percentage of correctly predicted compounds (70 %) are the most effective in comparison with regression (50 %) for the search for new antimicrobial agents in a number of derivatives of hybrids 1,2,4 triazole-3(2H)-thiol with pyrimidine fragment.